Peran Akuntansi Manajemen dalam Meningkatkan Kinerja Keuangan : Studi Kasus PT Sumber Alfaria Trijaya Tbk Tahun 2023-2024 - Nisa Monica Jong; Abdul Qodar Riyanto; Faiz Azzam Attamimi; Antonita Wahyu Cloria (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the extent to which management accounting plays a role in improving the financial performance of PT Sumber Alfaria Trijaya Tbk during the 2023–2024 period. Management accounting serves as a key function in providing financial and non-financial information used for planning, controlling, and making optimal business decisions. This research employs a descriptive qualitative approach using secondary data obtained from the company’s annual financial reports, management accounting books, and relevant scientific journals. The results show that the consistent implementation of management accounting contributes to cost efficiency, enhances budgeting processes, and supports more accurate decision-making. However, financially, there was a decline in profitability ratios, where ROA decreased from 10.17% to 8.30%, and NPM fell from 3.26% to 2.72%. Meanwhile, the DAR increased from 54.14% to 54.38%, and the CR rose from 100.36% to 104.48%, indicating an improvement in liquidity and capital structure stability. These findings suggest that although profitability experienced pressure due to higher operational costs, PT Sumber Alfaria Trijaya Tbk was able to maintain its liquidity and financial stability through effective budgeting systems and cost control mechanisms. Therefore, management accounting plays a significant role in the evaluation and continuous improvement of the company’s financial performance.